Preharvest UV-C Hormesis Induces Key Genes Associated With Homeostasis, Growth and Defense in Lettuce Inoculated With Xanthomonas campestris pv. vitians - Sidibé, Amadou; Charles, Marie Thérèse; Lucier, Jean-François; Xu, Yanqun; Beaulieu, Carole (Frontiers in Plant Science, 2022)
Preharvest application of hormetic doses of UV-C generates beneficial effects in plants. In this study, within one week, four UV-C treatments of 0.4 kJ/m2 were applied to three-week-old lettuce seedlings. The leaves were inoculated with a virulent strain of Xanthomonas campestris pv. vitians (Xcv) forty-eight hours after the last UV-C application. The extent of the disease was tracked over time and a transcriptomic analysis was performed on lettuce leaf samples. Samples of lettuce leaves, from both control and treated groups, were taken at 2 different times corresponding to T2, 48 h after the last UV-C treatment and T3, 24 h after inoculation (i.e. 72 h after the last UV-C treatment). A significant decrease in disease severity between the UV-C treated lettuce and the control was observed on days 4, 8 and 14 after pathogen inoculation. Data from the transcriptomic study revealed, that in response to the effect of UV-C alone and/or UV-C + Xcv, a total of 3828 genes were differentially regulated with fold change (|log2-FC|) > 1.5 and false discovery rate (FDR) < 0.05. Among these, of the 2270 genes of known function, 1556 were upregulated and 714 were downregulated. A total of 10 candidate genes were verified by qPCR and were generally consistent with the transcriptomic results. The differentially expressed genes observed in lettuce under the conditions of the present study were associated with 14 different biological processes in the plant. These genes are involved in a series of metabolic pathways associated with the ability of lettuce treated with hormetic doses of UV-C to resume normal growth and to defend themselves against potential stressors. The results indicate that the hormetic dose of UV-C applied on growing lettuce in this study, can be considered as an eustress that does not interfere with the ability of the treated plants to carry on a set of key physiological processes namely: homeostasis, growth and defense.